ANALISIS FAKTOR RASIO CAMEL TERHADAP PROFITABILITAS BANK PERKREDITAN RAKYAT DI PEKANBARU TAHUN 2008-2012 - Reychard Griha; Zulbahridar '; Raja Adri Satriawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to examine the effect of variable Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Operating Costs Operating Income (ROA), Loan to Deposit Ratio (LDR), and Net Interest Margin (NIM) of the Return on Assets (ROA) . The results of this study are expected to contribute to practitioners in maintaining the health of banks, especially rural banks (BPR).The data used is the publication of the Annual Report of Bank Indonesia from 2008 to 2012 sampling technique used was purposive sampling criteria rural banks (BPR) which has been operating in Pekanbaru during the period of observation the years 2008-2012 and submitted to Bank Indonesia. Obtained a sample of 11 company number rural banks (BPR)which has been operating in Pekanbaru during the observation period 2008-2012 The hypothesis was tested using t-statistics to test the significance of the partial regression coefficients and F-statistics to test the significance of regression coefficients together -sama at the 5% level of significance.The results of this study show that LDR is only one varabel partially significant effect on ROA in rural banks (BPR) which has been operating in Pekanbaru during the observation period in 2008 to 2012 with the degree of significance probability value 0.104> α 0.05. While partially CAR, NPL, ROA, NIM and PPAP not proven significant effect on ROA with the degree of significance probability value less than 0.05. The coefficient of determination indicates that the regression model was 66.6% ROA variable changes due to the six variables studied, while the remaining 33.4% is influenced by other factors not included in the research model. This study is confined to the profitability and liquidity ratios Rural Banks (BPR) with 77 samples of data and the annual observation period of 5 years. It is recommended that further research with other factors such as expanding the capital ratio, the ratio of management and sensitivity to market ratio, which is part of the CAMELS ratios as well as the elements of bank risk (risk) also need to be included as a predictor in predicting ROA in anticipation of the enactment of the Indonesian Banking Architecture (API) , so as to achieve a banking system, especially rural banks (BPR) is healthy, robust and efficient in order to create stability in the financial system in order to help drive the growth of the national economy.Keywords: Banks, Capital Adequacy Ratio, Liquidity, Profitability